Uptake of PPTCT services among HIV sero-positive pregnant women in Mumbai, India - A descriptive study - Shrikala Acharya; Roshni Cynthia Miranda; Padmaja Keskar (Elsevier, 2021)
Background: Prevention of parent to child transmission of HIV is a major programme to control the main cause of new HIV infections among children. The successful implementation of the programme requires timely linkages to testing, ART treatment, follow-up and care at various levels of the cascade. The study measures these key points in the Prevention of Parent to Child Transmission (PPTCT) programme which are crucial for achievement of elimination of neonatal HIV transmission. Methods: The study is a retrospective observational cohort study based on records of services provided to HIV sero-positive pregnant women enrolled for antenatal care at the 36 PPTCT centres across Mumbai during the period April 2014 to March 2015 and their follow-up till pregnancy outcome till October 2015. Results: In the Antenatal clinics, 1,20,892 pregnant women were tested for HIV during the study period, of which 520 (0.43%; 95% CI: 0.39-0.47) women tested positive. The median time of ANC registration is 22 weeks of gestation, median time to ART linkage following testing is 5 days and median duration of ART received by the ANC mother is 17.4 weeks. Of the total pregnancies (523), 85.1% resulted in live births, 3.1% were induced abortions, 2.5% ended in spontaneous abortions and 2.7% in still births. Conclusion: The successful implementation of the PPTCT programme is mainly dependent on the important linkages and follow-up for eliminating the transmission of HIV to newborns and for providing reproductive rights to HIV sero-positive parents without fear of transmitting the infection to the child.